Perbandingan Penanganan Kekerasan dalam Rumah Tangga (KDRT) di Indonesia dan Singapura - Eli Hendalia (Fakultas Hukum, Universitas Islam Bandung, 2011)
Comparison of Law in domestic violence between Indonesias with Singapore, has equality from second region culture of this state resides in South-East Asia, also is including country ASEAN, but also has difference from Luas Wilayah Singapura consisted of one main islands and around 60 isles with wide total 682,7 kilometre persegiTerletak between peninsulas Malayasia and Indonesia dissociated by strait Johor and Selat Singapura. Number Of Indonesia Residents is including the biggest in world after Chinese and India. Agreement of Member State ASEAN for ASEAN Charter as kontitusi ASEAN at Konf ( KTT) to 13 in Singapore November the year 2007. ASEAN as subject law ( has legal of personality.)